Nutrient presses and pulses differentially impact plants, herbivores, detritivores and their natural enemies. - Shannon M Murphy; Gina M Wimp; Danny Lewis; Robert F Denno (PLoS ONE, 2012)
Anthropogenic nutrient inputs into native ecosystems cause fluctuations in resources that normally limit plant growth, which has important consequences for associated food webs. Such inputs from agricultural and urban habitats into nearby natural systems are increasing globally and can be highly variable, spanning the range from sporadic to continuous. Despite the global increase in anthropogenically-derived nutrient inputs into native ecosystems, the consequences of variation in subsidy duration on native plants and their associated food webs are poorly known. Specifically, while some studies have examined the effects of nutrient subsidies on native ecosystems for a single year (a nutrient pulse), repeated introductions of nutrients across multiple years (a nutrient press) better reflect the persistent nature of anthropogenic nutrient enrichment. We therefore contrasted the effects of a one-year nutrient pulse with a four-year nutrient press on arthropod consumers in two salt marshes. Salt marshes represent an ideal system to address the differential impacts of nutrient pulses and presses on ecosystem and community dynamics because human development and other anthropogenic activities lead to recurrent introductions of nutrients into these natural systems. We found that plant biomass and %N as well as arthropod density fell after the nutrient pulse ended but remained elevated throughout the nutrient press. Notably, higher trophic levels responded more strongly than lower trophic levels to fertilization, and the predator/prey ratio increased each year of the nutrient press, demonstrating that food web responses to anthropogenic nutrient enrichment can take years to fully manifest themselves. Vegetation at the two marshes also exhibited an apparent tradeoff between increasing %N and biomass in response to fertilization. Our research emphasizes the need for long-term, spatially diverse studies of nutrient enrichment in order to understand how variation in the duration of anthropogenic nutrient subsidies affects native ecosystems.